Viral mitochondriopathy in COVID-19 - Tsung-Hsien Chen; Tien-Hsin Jeng; Ming-Yang Lee; Hsiang-Chen Wang; Kun-Feng Tsai; Chu-Kuang Chou (Redox Biology)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), disrupts cellular mitochondria, leading to widespread chronic inflammation and multi-organ dysfunction. Viral proteins cause mitochondrial bioenergetic collapse, disrupt mitochondrial dynamics, and impair ionic homeostasis, while avoiding antiviral defenses, including mitochondrial antiviral signaling. These changes drive both acute COVID-19 and its longer-term effects, known as “long COVID”. This review examines new findings on the mechanisms by which SARS-CoV-2 affects mitochondria and for the impact on chronic immunity, long-term health risks, and potential treatments.